INTEGRASI MEKANISME DIVERSI DENGAN KEARIFAN LOKAL SUKU MARIND DALAM PENYELESAIAN TINDAK PIDANA YANG DILAKUKAN ANAK ASLI PAPUA - Alputila, Marlyn Jane (Jurnal Restorative Justice, 2025)
This research aims to analyze the juridical synchronization between the diversion mechanism as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) and the child case resolution procedures according to the customary law of the Marind Tribe in South Papua Province. Utilizing a socio-legal research method analyzed through Legal Pluralism Theory and Restorative Justice Theory, the results indicate that philosophically, there is an alignment of values between the principles of national restorative justice and the local wisdom of the Marind Tribe, both of which prioritize the restoration of social balance. However, juridically and normatively, a significant obstacle exists in the formal requirements of Article 7, Paragraph (2) of the SPPA Law, which restricts diversion only to offenses punishable by less than seven years of imprisonment. This creates a legal gap where customary settlements completed at the community level are often not legally recognized within the formal judicial administration. This study concludes that procedural synchronization can only be achieved by optimizing the Papua Special Autonomy Law as a juridical bridge to provide discretion for the implementation of Marind customary law within the national juvenile criminal justice system. Keywords: Diversion, Indigenous Papuan Children, Marind Tribe, South Papua, Juridical Synchronization.